The Political Cognition of Young Entrepreneurs - Brenda Putri Defaky; Zakwan Adri (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the increasing involvement of youth in entrepreneurship and politics, reflecting a complex relationship between economic agency and political participation. However, research specifically examining youth political cognition within entrepreneurial contexts, particularly after experiences of political failure, remains limited. This study aims to analyze how youth political cognition is formed in entrepreneurial contexts, identify the factors influencing youth engagement in entrepreneurship and politics, and explore how young individuals interpret the relationship between these domains. A qualitative approach with a phenomenological design was employed to examine lived experience. The research participant was a young entrepreneur with prior political involvement, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model, comprising data condensation, data display, and conclusion drawing. The findings reveal that youth political cognition is constructed through an integrated process involving perception, memory, information processing, thinking, problem-solving, and metacognition. Politics is interpreted as both an opportunity and a risk within entrepreneurial activity, while past political experience serves as a basis for decision-making supported by critical and adaptive thinking. The study also finds that political involvement influences business dynamics, generating both positive and negative impacts. The study concludes that political cognition plays a significant role in shaping young entrepreneurs’ capacity to adapt, make strategic decisions, and develop entrepreneurial ventures within complex socio-political environments. Its contribution lies in integrating political cognition and entrepreneurship perspectives while offering practical insights for youth and policymakers in developing adaptive strategies and supportive policy frameworks.